Predictors of e-learning satisfaction in teaching and learning for school teachers: a literature review - Cheok, Mei Lick; Wong, Su Luan (International Journal of Instruction, 2015)
This paper develops a theoretical model of the determinants of e-learning satisfaction in teaching and learning among secondary school teachers. It is based on reviews of past studies on satisfaction in using information technology systems. Three potential groups of determinants of satisfaction among secondary school teachers were identified; user-related characteristics, organisational-related characteristics and the e-learning-system characteristics. Usage is established as a mediating variable between the three potential groups of determinants and satisfaction towards e-learning. Future research could provide a more definitive theoretical statement of e-learning satisfaction and develop an additional proposition which could be derived from a more refined theory. The research yields a theoretical framework that outlines the predictive potential of the three groups of key factors in explaining e-learning satisfaction among secondary school teachers. The factors can be considered when developing future continuous professional development courses and intervention programmes when proposing a new innovation in the curriculum.